Novel Gastroprotective and Thermostable Cocrystal of Dimethyl Fumarate: Its Preparation, Characterization, and In Vitro and In Vivo Evaluation - Alam Q.; Ganeshpurkar A.; Singh S.K.; Krishnamurthy S. (My University, 2025)
Crystallization has revolutionized the field of solid-state formulations by modulating the physiochemical and release profile of active pharmaceutical ingredients (APIs). Dimethyl fumarate (DF), an FDA-approved first-line drug for relapsing-remitting multiple sclerosis, has a sublimation problem, leading to loss of the drug during its processing. To tackle this problem, DF cocrystal has been prepared by using solvent evaporation technique using nicotinamide as a coformer, which has been chosen based on in silico predictions and their ability to participate in hydrogen bonding. Fourier transform infrared (FT-IR), powder X-ray diffraction (PXRD), thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), and sublimation analysis have characterized the cocrystal and its thermostability. Comparative analysis of the release profile has been done by the dissolution and pharmacokinetic study of DF and its cocrystal. Formulated cocrystal is noncytotoxic, antioxidant and inhibits interleukin-6 and tissue necrosis factor-α in peripheral blood mononuclear cells induced by lipopolysaccharide. We have obtained a thermostable cocrystal of DF with a similar physicochemical and release profile to that of DF. The formulated cocrystal also provides a gastroprotective effect which helps counterbalance the adverse effects of DF by reducing lipid peroxidation and total nitrite levels. © 2023 The Authors. Published by American Chemical Society.